PENGARUH MODEL PEMBELAJARAN PROBLEM SOLVING TERHADAP MOTIVASI BELAJAR DAN KEMAMPUAN PEMAHAMAN KONSEP MATEMATIKA SISWA KELAS VIII SMPN 8 BUKITTINGGI TAHUN PELAJARAN 2025/2026 - Eldoracaesar Noli, Melati; Rusdi, Rusdi; Rahmat, Tasnim; Fitri , Haida (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Learning motivation and the ability to understand mathematical concepts are important competencies in learning. However, PISA results indicate that students' mathematical conceptual understanding remains low. This finding is further supported by preliminary research and several previous studies in Indonesia, including the researcher's initial study at SMPN 8 Bukittinggi. Based on observations and interviews with teachers and students, it is suspected that the low learning motivation and mathematical conceptual understanding of students at SMPN 8 Bukittinggi are caused by the teacher-centered learning process, which leads to students being less active and tending to memorize procedures without understanding the concepts, thus experiencing difficulties in understanding mathematical concepts. The researcher attempted to implement a problem-solving learning model to address these issues. The purpose of this study was to determine whether there is a significant effect of the problem-solving learning model on the motivation and mathematical conceptual understanding of eighth-grade students at SMPN 8 Bukittinggi. This study was a pre-experimental study using the Static Group Comparison Design (GDC). The population was three eighth-grade students at SMPN 8 Bukittinggi. The sample consisted of students in grades VIII.3 and VIII.2, respectively. Sampling was conducted using the Simple Random Sampling technique after conducting tests for normality, homogeneity of variance, and equality of means on the data population. The instruments in this study were a motivation questionnaire and a test for understanding mathematical concepts. The data analysis technique used the t-test. After passing the prerequisite tests for normality and homogeneity. Based on the results of the data analysis of motivation and students' mathematical concept understanding abilities at the α = 0.05 level using the t-test, for learning motivation, the calculated t>ttable was 6.13>1.67. Then, reviewed again using Minitab Software, the P-value was obtained = 0.000 <α = 0.05, so H0 was rejected and H1 was accepted. Meanwhile, for conceptual understanding abilities, the calculated t>ttable was 5.006>1.67, which was also seen using Minitab Software, the P-value was obtained = 0.000 <α = 0.05, H0 was rejected and H1 was accepted. So, it can be concluded that there is a significant influence of the problem solver learning model on learning motivation and the ability to understand mathematical concepts of class VIII students of SMPN 8 Bukittinggi in the 2025/2026 academic year.